THE EFFECT OF SOAKING IN THE ALOEVERA EXTRACT SOLUTION ON THE SHELF-LIFE OF DRIED CATFISH (Pangasius hypopthalmus) - Franklin Yobel Sitohang; Dewita Dewita; Suparmi Suparmi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT Theaim of the study was to know the effect of adding aloevera extract on the shelf-life of dried catfish. The method used was experiment and the design used was a non factorial randomized block design(RBD). The treatments conducted were soaking the catfish into aloevera extract solution, varied to four level (0, 25 mL, 35 mL, and 45 mL), for three hours. The samples then were stored and observed for 10, 20 and 30 days. The parameters used were the total number of microba (total plate count), chemical analysis(the content of moisture, protein, and fat) and organoleptic values (appearance, odor, taste  and texture). The result showed that all level of aloevera extract solutionwere affecting significantlyto the appearace, odor, texture,total plate countand fat content, but not significantly tothemoisture and protein content. The soaking the catfish into the aloevera extract solution at 45 ml wasshowing the best treatment, indicated by highest values of organoleptic evaluation. The dried catfish was performing the appearance with whole, bright colour and tight skin;the texturewas compact, solid, and elastic;and the odor was specific smell of fresh fish. The total number of microbia was 2.6 x 105CFU/g, moisture content was 19.95%, fat content was 67.27% andprotein content was 66.75%. Key words :aloeveraextract, dried catfish, immersion, shelf life,